Neurochemical Mechanisms in Disease - Blass, John P.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This volume of Advances in Neurobiology deals with the Neurochemistry of disease, with chapters covering both human diseases and animal (3z(Bmodel(3y (Bdisorders. Specific diseases are covered in chapters on neurodegenerations such as Alzheimer$1 (Bs and Parkinson's, on demyelinating diseases, on autism, and so on. This volume on Neurochemical Mechanisms in Disease strives to encourage more chemically based definitions of these and other diseases.s
Mechanisms versus Diagnoses -- Molecular Mechanisms of Neuronal Death -- Animal Models of Neurodegenerative Diseases -- Vitamins and Vitamin Deficiencies -- Brain Edema in Neurological Disease -- Pathology of Monoamine Transporters -- Glutamate and Glutamine in Brain Disorders -- The X-linked Mental Retardation -- Cognitive Deficits in Neurodegenerative Disorders -- NFkappaB in Brain Diseases -- Trinucleotide-Expansion Diseases -- Neuroinflammation -- Neurochemistry of Autism -- RNA Pathologies in Neurological Disorders -- Pain -- Biology of Demyelinating Diseases -- Brain Protein Oxidation and Modification for Good or Bad in Alzheimer$1 (Bs Disease -- Oxidative Stress and Alzheimer Disease: Mechanisms and Therapeutic Opportunities -- Tau and Tauopathies -- Zinc, Zinc Transport and Sequestration Proteins in the Brain in the Progression of Alzheimer$1 (Bs Disease -- The Genetics of Alzheimer$1 (Bs Disease and Parkinson$1 (Bs Disease -- Nicotine Receptors in Brain Diseases -- Lysosomal Storage Disorders -- Genetic signaling in glioblastoma multiforme: a current overview.s
Keywords: Medicine; Neurosciences; Biomedicine; Neurosciences